2016
DOI: 10.1111/cfs.12274
|View full text |Cite
|
Sign up to set email alerts
|

‘I want to be better than you:’ lived experiences of intergenerational child maltreatment prevention among teenage mothers in and beyond foster care

Abstract: The growing body of research on teenage motherhood in foster care has largely focused on the risks involved for both mother and child, yet these mothers depict a much more complex picture of their own experience of becoming and being mothers. The current study employed interpretative phenomenological analysis to explore 18 in-depth, qualitative interviews from six participants on the meaning and experience of motherhood among teenage mothers in foster care and in the years immediately after ageing out. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 27 publications
0
43
0
Order By: Relevance
“…Complementing Max & Paluzzi's () findings, providers suggested that mothers often lacked the ability to identify, let alone establish healthy relationships. As with earlier work (Aparicio In press), mothers recognized they should not emulate their own parent‐child relationships with their children. Also, they felt that although their child's father was far from ideal, he was ‘there’ sometimes when they needed assistance.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…Complementing Max & Paluzzi's () findings, providers suggested that mothers often lacked the ability to identify, let alone establish healthy relationships. As with earlier work (Aparicio In press), mothers recognized they should not emulate their own parent‐child relationships with their children. Also, they felt that although their child's father was far from ideal, he was ‘there’ sometimes when they needed assistance.…”
Section: Discussionmentioning
confidence: 63%
“…Mothers ageing out of the child welfare system have much to gain from social capital (Connolly et al ; Aparicio In press). This study examined social support among mothers ageing out from the perceptions of both mothers and service providers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One explanation could be that socially accepted standards regarding the “good mother” have a pervasive impact among these women who feel they are perceived as unfit, because of their history of being in care. Indeed, qualitative explorations of former welfare/justice‐involved women on their experiences of parenthood highlighted generalized beliefs that they are expected to fail as mothers and that they are parenting under surveillance (Aparicio, ; Connolly et al, ; Maxwell et al, ; Pryce & Samuels, ). Such a mistrust of others and perceived stigma might very well be founded.…”
Section: Introductionmentioning
confidence: 99%